BRICS: World heavyweight in agricultural trade - Thomas Glauben; Ivan Djuric (Intereconomics, 2024)
BRICS, the 15-year-old alliance of Brazil, Russia, India, China and South Africa, has emerged as an important actor on the global political and economic stage, not least by expanding its membership to include middle-power states Egypt, Ethiopia, Iran, Saudi Arabia and the United Arab Emirates in early 2024. Much like the countries of the G7 and the EU, BRICS members are among the major players in international agri-food markets. BRICS and the G7 have accounted for around one-seventh of each other's agricultural exports in the past decade. However, excessive protectionism and mounting sanctions as well as ideology-driven de-risking strategies are a high-risk venture that could ultimately lead to isolationism and the formation of blocs. Food insecurity is growing, primarily at the expense of poorer people in the Global South. Against this background, it seems advisable to balance geopolitical and geoeconomic interests by turning away from confrontational Stone Age politics and towards more cooperative approaches, such as more diplomacy.
Keywords: F02; Q17; O19; 330; Land trade; Food security; BRICS countries; Landhandel; Ernährungssicherung; BRICS-Staaten